The Impact of Administrative Transparency on the Relationship between Internal Marketing Policies and the Job Satisfaction of the Internal Customer: An Applied Study at Taif University - Kingdom of Saudi Arabia - Alghamdi, Abdulraheem Ali; Alfarran, Abeer Kamel (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to identify the extent of the practice of internal marketing policies and administrative transparency at Taif University, and its impact on the level of internal customer satisfaction (employee). As well as to observe the mediating effect of administrative transparency in the relationship between internal marketing policies and internal customer satisfaction. This study attempts to fill the gap in previous studies related to the impact of internal marketing policies (independent variable) and administrative transparency (intermediate variable) on enhancing internal customer satisfaction (dependent variable) in Saudi universities. A descriptive-analytical approach was used, and 254 questionnaires were distributed randomly stratified to the study sample. The number of valid questionnaires for analysis was (125), which were analysed using the statistical program (SPSS). The findings were that there was a medium degree of approval towards each of the dimensions of internal marketing, the practice of administrative transparency and internal customer satisfaction. There was also a relationship and impact between internal marketing policies and internal customer satisfaction. Similarly, there was a relationship and impact between administrative transparency and internal customer satisfaction. There were a relationship and impact between internal marketing policies and administrative transparency. Moreover, it found that administrative transparency strengthens the positive relationship between internal marketing policies and internal customer. This study recommended increasing employees’ job satisfaction by implementing an effective system of incentives and rewards, training and development and promotions. Furthermore, universities should improve the level of administrative transactions and communications, financial facilitation, and good relations among employees. Moreover, they have to adopt the concept of internal marketing by meeting the needs of employees and working on developing them. Finally, they have to tout administrative transparency policies, as well as clarifying the reasons for administrative decisions with stability and ease of understanding in order to build credibility and trust with employees.